Share Premium, IPO Overvaluation and Post-IPO Underperformance in an Emerging Markets: Evidence from Indonesia's Acceleration Board - Ganda, Maurice; Tanzil, Nanny Dewi; Wahyuni, Ersa Tri (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study investigates whether IPO valuation indicators predict the long-term post-IPO performance of companies listed on the Indonesia Stock Exchange (IDX) Acceleration Board. The study examines the effects of Price-to-Book Value (PBV), Price-to-Earnings Ratio (PER), Trading Volume Ratio (TVR), and Share Premium Ratio on post-IPO stock returns. Using a quantitative explanatory and predictive research design, this study analyzed the entire population of 43 Acceleration Board IPO firms listed between 2020 and 2024. Data were analyzed through descriptive statistics, Pearson correlation, multiple linear regression, binary logistic regression, and machine learning models. including Decision Tree and Random Forest for predictive analytics. The results reveal that more than two-thirds of Acceleration Board IPO firms experienced negative post-IPO returns across the 360-, 720-, and 1,080-day observation periods, indicating widespread long-term underperformance. However, the selected valuation indicators demonstrate limited explanatory and predictive power, with only PBV showing a significant positive association with 720-day returns. Overall, the findings suggest that long-term IPO performance is influenced by broader firm-specific and market-related factors beyond initial valuation metrics. The study also shows that Share Premium Ratio is not reliable indicator of IPO overvaluation, as it primarily reflects the legal and administrative structure of IPO pricing rather than firms’ intrinsic economic value.